Engaging indigenous knowledge(s) in research and practice - Sue, McGinty (Penerbit UKM, 2012)
Researching education for students of Indigenous Studies means addressing the philosophical, theoretical and practical questions that arise when a researcher from one culture begins research with people from another language and culture. Specifically,Indigenous peoples across the world contest research that frames them within a deficit discourse, as well as research that is done ‘on them’ rather than ‘with them’. Indigenous people have advocated for their ontologies and epistemologies to be recognised within the academy, alongside the Western Canon of knowledge and research processes. In this context, this paper will address three issues of importance for non-Indigenous researchers working with Indigenous peoples. Firstly, preparing yourself to do Indigenous research by being a top quality researcher yourself and, when invited, to learn from Indigenous peoples about their knowledges. This is, of course, regulated by factors such as gender,age, expertise and relationships with Indigenous peoples. Secondly, preparing Indigenous students to become top quality researchers themselves, seeking opportunities to create new knowledge in that culturally diverse space. This includes challenging the boundaries of the academy to include Indigenous knowledges and practices in thesis production (McGinty, Koo, & Saeidi, 2010). Thirdly, preparing non-Indigenous students to do quality Indigenous research which includes knowing your limitations, having a commitment to building Indigenous research capacity and operating in an environment of deep respect for those you are working with. Examples from research projects and student theses will illustrate these issues.